Current practices in home mechanical ventilation for chronic obstructive pulmonary disease: A real-life cross-sectional multicentric study - Ribeiro, C. (2021)
Home mechanical ventilation (HMV) use in chronic obstructive pulmonary disease (COPD) is becoming increasingly widespread. The aim of this study was to provide an accurate description of the current practices and clinical characteristics of COPD patients on HMV in Portugal. The study was designed as a cross-sectional, multicenter real-life study of COPD patients established on HMV for at least 30 days. Data related to clinical characteristics, adaptation and ventilatory settings were collected. The study included 569 COPD patients on HMV from 15 centers. The majority were male, with a median age of 72 years and a high prevalence of obesity (43.2%) and sleep apnea (45.8%). A high treatment compliance was observed (median 8h/day), 48.7% with inspiratory positive airway pressure ≥ 20 cmH2O and oronasal masks were the preferred interface (91.7%). There was an equal distribution of patients starting HMV during chronic stable condition and following an exacerbation. Patients in stable condition were initiated in the outpatient setting in 92.3%. Despite the differences in criteria and setting of adaptation and a slightly lower BMI in patients starting HMV following an exacerbation, we found no significant differences regarding age, gender, ventilation pressures, time on HMV, usage, severity of airflow obstruction or current arterial blood gas analysis (ABGs) in relation to patients adapted in stable condition. Patients were highly compliant with the therapy. In agreement with most recent studies and recommendations, there seems to be a move towards higher ventilation pressures, increased use of oronasal masks and an intent to obtain normocapnia. This study shows that chronic hypercapnic and post exacerbation patients do not differ significantly regarding patient characteristics, physiological parameters or ventilatory settings with one exception: chronic hypercapnic patients are more often obese and, subsequently, more frequently present OSA.